PERAN KOMUNIKASI SEBAGAI PENDUKUNG PERUBAHAN ORGANISASI - Benedicta Evienia Prabawanti (Bina Ekonomi, 2008)
Every changing in organization potentially produces some conflicts because it make unpredictable situation for every elements and members of organization. The changing causes a problem if it is not communicated effectively to them. They accept the organizational changing only if they know and realize that changing is important for organizational development and surviving in its environment. They must be informed that they are not be worsen but advantaged because it. The communication must be done before, during, and after the changing of organization to make the changing move smoothly. This article describes the communication role in the changing of organization. it employs cases of two companies as examples of the communication role in smooth and effective change in organization that make them go to the better situation.